(untitled) (Studia austriaca, 2013)
Drawing on the concept of contingency this paper aims at analyzing Ransmayr’s concept of fictional and historiographical narrative as it is formulated in his first novel and later poetological texts. Ransmayr’s “geographical poetics” is also explored. In his text Geständnisse eines Touristen (2004) Ransmayr describes the process of writing by developing a whole network of geographical metaphors. These can be read in connection to Die Schrecken des Eises und der Finsternis, which, as a novel about travel and writing, seems to be an important resource for Ransmayr’s later theoretical text.